Aestheticizing suffering: Evaluative stance in pulitzer-winning photos of refugees' crisis in Europe. (April 2019) - Fawzy, Rania Magdi
Abstract: News photos of refugees and migrants tend to be highly evaluative since they capture the moments of human suffering, vulnerability and helplessness. Informed by the works of Martin and White (2005) and Economou (2009, 2008) on Appraisal Theory and evaluative stance, the current paper identifies the visual evaluative resources in Reuters ' Pulitzer-winning photos of refugees and migrants' crisis in Europe for the year 2016. When considering photos evaluative stance, this paper argues, news photos should not be merely viewed as witness or proof of the events, rather they should be acknowledged for their aesthetic properties and compositional perspectives. This marks the importance of introducing delicate refinements to Martin and White's (2005) APPRECIATION model by adding, replacing and removing subcategories to account for the range of visual resources deployed in the photos under discussion. Photos' visual cues and semiotics codes are added to the APPRECIATION model. Doing so, a distinction between the evaluative stances infused by photos aesthetical properties and those arising from photos'content and the depicted participants is established. Two authorial voices are then proposed: the Witness voice and the Artist voice. The delicate modifications introduced to the APPRECIATION model helps to dig deep into the embedded evaluative stance of the photos. Applying the suggested APPRECIATION resources, it is found that Pulitzer-winning photos aestheticize the suffering of the refugees and render it beautiful and photogenic. However, the evoked positive APPRECIATION resources instantiate negative JUDGEMENT values of social exclusion, impersonalization, and Otherness.